Assessment of welfare and health of dairy cows under different housing and management systems - Ahmed.S. Mostafa (Egyptian Society for Animal Management, 2016)
This study was conducted in six dairy farms in Beni-Suef Governorate representing the most prevalent systems of housing and management in Egypt to assess the welfare and health of dairy cows kept in these systems. These systems including 1) tie stall barn with daily access to an outside shaded area associated with hand milking twice daily; 2) loose housing in partially sheltered yards on earthy floor represented by 4 farms with different management practices include feeding and milking, and 3) free stall barn with daily access to partially sheltered yards during the day time associated with three times daily milking in a parlour system. Each farm was visited three times over a period of one year. All cows were observed for lying and standing up behaviour and examined for lameness, mastitis, skin alterations at the knee and hock joints and rest of the body, teat injuries, cleanliness of the hind legs and udder, and body condition score. Results revealed that no restriction for lying and standing up behaviour was observed in all systems indicating that cow comfort was maintained. The prevalence of lameness was higher in loose housing system on earthy floor (0.9, 15.4 and 8.7 %). The prevalence of skin alterations at the knee joint was higher in cows kept in tie and free stall barns (4.7 and 7.5 % respectively) and at hock joints (11.9 %) in tie stall barn on concrete floor. Tie stall system had a higher prevalence of teat injuries (14.3 %) than other systems. High degree of dirtiness of hind legs (90.5, 89 and 99.2 %) and udder (91.4, 91.6 and 100 %) was found in loose housing system associated with increased dampness of the floor and lack of daily cow cleaning regimen.